2022
DOI: 10.3390/en15113933
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Based Climate Emissions of Charcoal Conditioning Routes for the Use in the Ferro-Alloy Production

Abstract: Renewable reductants are intended to significantly reduce CO2 emissions from ferro-alloy production, e.g., by up to 80% in 2050 in Norway. However, charcoals provide inferior properties compared to fossil fuel-based reductants, which can hamper large replacement ratios. Therefore, conditioning routes from coal beneficiation was investigated to improve the inferior properties of charcoal, such as mechanical strength, volatile matter, CO2 reactivity and mineral matter content. To evaluate the global warming pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 117 publications
(204 reference statements)
0
1
0
Order By: Relevance
“…The study by Surup et al [87] indicated that LCA can reduce global warming by 5 % to 10 %. This implies the need to reduce the global warming potential of carbon reducers by 80 to 90 % compared to metallurgical Coke.…”
Section: Materials Communitymentioning
confidence: 99%
“…The study by Surup et al [87] indicated that LCA can reduce global warming by 5 % to 10 %. This implies the need to reduce the global warming potential of carbon reducers by 80 to 90 % compared to metallurgical Coke.…”
Section: Materials Communitymentioning
confidence: 99%
“…The objective of this work was to compare the environmental performance of fossilbased and renewable injecting materials employed as carbon sources in the EAF steelmaking process. To the best of the authors' knowledge, despite many studies on the environmental impact of steel production [13][14][15], there is a lack of life cycle assessment studies on the use of hydrochar in the EAF steelmaking process based on an industrial scale [16][17][18]. This work was aimed at providing insights into the potential application of bio-based carbon material in the steelmaking process in order to reduce its overall environmental impact.…”
Section: Goal and Scopementioning
confidence: 99%
“…Life cycle assessment (LCA) is a standardized framework for assessing the environmental impacts of a product or process at every stage of its life cycle, from manufacture to disposal. Despite the several studies dealing with the environmental impact of steel production [13][14][15], there is a lack of LCA studies on the use of biocarbon in the EAF steelmaking process [16][17][18]. This study aimed to provide a comprehensive assessment of the environmental impacts of steel produced using electric arc furnaces that employ pulverized hydrochar as charged and injected material as a substitute for fossil coal.…”
Section: Introductionmentioning
confidence: 99%